2017
DOI: 10.1128/aem.00995-17
|View full text |Cite
|
Sign up to set email alerts
|

Indole-Induced Reversion of Intrinsic Multiantibiotic Resistance in Lysobacter enzymogenes

Abstract: species are a group of environmental bacteria that are emerging as a new source of antibiotics. One characteristic of is intrinsic resistance to multiple antibiotics, which had not been studied. To understand the resistance mechanism, we tested the effect of blocking two-component regulatory systems (TCSs) on the antibiotic resistance of, a prolific producer of antibiotics. Upon treatment with LED209, an inhibitor of the widespread TCS QseC/QseB, produced a large amount of an unknown metabolite that was barely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…However, two studies reported that indole decreases antibiotic resistance in the Gramnegative Lysobacter species by stimulating the vitamin B12 importer BtuD [37,38]. The weak selectivity of the importer causes cells to increase antibiotic uptake, resulting in cell death [38].…”
Section: Indole Signalling and Antibiotic Resistancementioning
confidence: 99%
“…However, two studies reported that indole decreases antibiotic resistance in the Gramnegative Lysobacter species by stimulating the vitamin B12 importer BtuD [37,38]. The weak selectivity of the importer causes cells to increase antibiotic uptake, resulting in cell death [38].…”
Section: Indole Signalling and Antibiotic Resistancementioning
confidence: 99%
“…A recently study of ours reported that indole is able to reverse the intrinsic antibiotic resistance of Lysobacter through the two-component regulatory system QseC/QseB. Site-specific mutations in the qseC gene also resulted in antibiotic susceptibility (36). Besides, this antibiotic resistance reversal was facilitated by a novel BtuD-associated importer which can transfer both vitamin B12 and antibiotics (37).…”
mentioning
confidence: 83%
“…Extraction of plasmids and DNA fragments was performed following the instructions included with the kits purchased from Omega (plasmid mini kit I and gel extraction kit, Omega USA). All molecular manipulations were carried out according to methods described previously (30, 36). Restriction enzymes and molecular biology reagents were purchased from TaKaRa (TaKaRa Bio Group, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Another salient feature of Lysobacter spp. is their intrinsic resistance to multiple antibiotics (30). However, the molecular mechanism underlying this intrinsic antibiotic resistance is not well understood, possibly because Lysobacter spp.…”
Section: Introductionmentioning
confidence: 99%